PENGARUH PENGENDALIAN INTERNAL DALAM SISTEM AKUNTANSI PENGGAJIAN TERHADAP PERILAKU ETIS KARYAWAN : (Studi Kasus Satuan Kerja Pelaksanaan Jalan Nasional Wilayah IV. Provinsi NTT-PPK 6.2 Ruas Ende-Wolowaru) - Ratu, Agustina Dagu; Banda, Falentina Lucia; Ismail, Nuraini (Jurnal Riset Ilmu Akuntansi, 2020)
This study aims to determine the effect of internal control in the payroll accounting system on employee ethical behavior. This research is a quantitative approach research with the research object of the National Road Implementation Unit IV Region. NTT Province KDP 6.2 Ende-Wolowaru Section. The population in this study is the National Road Implementation Unit IV Region. NTT Province KDP 6.2 Ende-Wolowaru Section. The sample of this research is contract workers of PPK 6.2 Ende-Wolowaru segment. The research data is primary data obtained directly through the research questionnaire which was distributed to 30 respondents. The variables of this study consisted of independent variables, namely internal control of the payroll accounting system and the dependent variable was the ethical behavior of employees, the data analysis used simple linear regression after the data was collected, the data were analyzed using the SPSS 21 program. The results showed that the internal control variable significantly influenced the ethical behavior of employees.